Effects of oxygen plasma treatment on the formation of ohmic contacts to GaN and AlGaN - Yan, J; Kappers, M; Crossley, A; McAleese, C; Phillips, W; Humphreys, C (2004)
The effects of oxygen plasma treatment prior to metal contact deposition have been studied for both n-and p-GaN, as well as n-AlGaN. In n-GaN, the as-deposited Ti/Al contacts change from rectifying to ohmic, and further improvements are observed after rapid thermal annealing (RTA). A specific contact resistivity better than 10-7 Ω cm2 was obtained using a plasma treatment of 20 s at 30 W and 0.2 mbar, followed by RTA at 500 °C in argon. The I-V characteristics of the Ti/Al contacts degraded when plasma treatments were performed for a longer time and/or at increased plasma pressure. However, in contrast to n-GaN, the electrical properties of the Ni/Au contacts to p-GaN and Ti/Al contacts to n-Al0.15Ga 0.85N deteriorated following oxygen plasma treatment. X-ray photoelectron spectroscopy (XPS) was used in order to help elucidate the mechanisms behind these effects. © 2004 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.